The Challenges and Strategies to Improve Family-centered Round: A Literature Review - Utami, Reni Sulung (Nurse Media Journal of Nursing, 2012)
The importance of family-centered care and the role of families in decision making are becoming more recognized today. Several studies have supported the implementation of family-centered care and its role in enhancing quality of care. Family-centered rounds are one of family centered model of care that brings together multidisciplinary team as well as family to discuss the patient’s condition and care management, coordinate the patient’s care management, and make decisions on care plan for the patient (Sisterhen et al., 2007, Aronson et al., 2009). As part of innovations to enhance family-centered care, family-centered rounds have been adopted and implemented in many hospitals. This model of rounds is popular and widely applied in the neonatal and pediatric intensive care unit (Aronson et al., 2009, Kleiber et al., 2006, Mittal et al., 2010). However, other units have also begun to implement it (Schiller and Anderson, 2003, Mangram et al., 2005). The benefits of family-centered rounds have been presented in several studies. They reported that family-centered rounds have been improved communication between staff and family members (Mittal et al., 2010, Jacobowski et al., 2010, Rosen et al., 2009, Vazirani et al., 2005), understanding of the patient’s care plan (Rosen et al., 2009), staff and family satisfaction (Rappaport et al., 2010, Rosen et al., 2009); and decreased need for care plan clarification (Rosen et al., 2009).